Busulfan or Treosulfan Conditioning Platform for Allogeneic Stem Cell Transplantation in Patients Aged >60 Y With Acute Myeloid Leukemia/Myelodysplastic Syndrome: A Subanalysis of the GITMO AlloEld Study. Issue 3 (22nd February 2023) - Malagola, Michele; Polverelli, Nicola; Martino, Massimo; Patriarca, Francesca; Bruno, Benedetto; Giaccone, Luisa; Grillo, Giovanni; Bramanti, Stefania; Bernasconi, Paolo; De Gobbi, Marco; Natale, Annalisa; Terruzzi, Elisabetta; et al.
Abstract : Background: The conditioning regimens with different alkylators at different doses can influence the outcome of allogeneic stem cell transplantation (SCT), but conclusive data are missing. Methods: With the aim to analyze real-life allogeneic SCTs performed in Italy between 2006 and 2017 in elderly patients (aged >60 y) with acute myeloid leukemia or myelodysplastic syndrome, we collected 780 first transplants data. For analysis purposes, patients were grouped according to the type of alkylator included in the conditioning (busulfan [BU]-based; n = 618; 79%; treosulfan [TREO]-based; n=162; 21%). Results: No significant differences were observed in nonrelapse mortality, cumulative incidence of relapse, and overall survival, although in the TREO-based group, we observed a greater proportion of elderly patients ( P  < 0.001); more active diseases at the time of SCT ( P  < 0.001); a higher prevalence of patients with either hematopoietic cell transplantation-comorbidity index ≥3 ( P  < 0.001) or a good Karnofsky performance status ( P  = 0.025); increased use of peripheral blood stem cells as graft sources ( P  < 0.001); and greater use of reduced intensity conditioning regimens ( P  = 0.013) and of haploidentical donors ( P  < 0.001). Moreover, the 2-y cumulative incidence of relapse with myeloablative doses of BU was significantly lower than that registered with reduced intensity conditioning (21% versus 31%; P  = 0.0003). This was not observed in the TREO-based group. Conclusions: Despite a higher number of risk factors in the TREO group, no significant differences were observed in nonrelapse mortality, cumulative incidence of relapse, and overall survival according to the type of alkylator, suggesting that TREO has no advantage over BU in terms of efficacy and toxicity in acute myeloid leukemia and myelodysplastic syndrome.